PENGARUH FINANCIAL DISTRESS, GROWTH OPPORTUNITY, KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, DEBT COVENANT, DAN INTENSITAS MODAL TERHADAP KONSERVATISME AKUNTANSI - Aprialdano Arjuna Jaya; Maria (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to empirically examine the effect of Financial Distress, Growth Opportunity, Institutional Ownership, Managerial Ownership, Debt Covenant, and Capital Intensity on Accounting Conservatism in IDX Manufacturing Companies 2018-2020. This study uses the purposive sampling technique for sampling. The study was conducted with a total of 30 samples of manufacturing companies from a total population of 90 companies. The results of this study are Institutional Ownership, Managerial Ownership, Debt Covenant do not affect the application of accounting conservatism. Growth opportunities and capital intensity positively influence the application of accounting conservatism. Financial Distress has a negative effect on accounting conservatism.